2004
DOI: 10.1091/mbc.e04-03-0179
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin and Troponin Are Required for Ovarian Contraction in theCaenorhabditis elegansReproductive System

Abstract: Ovulation in the nematode Caenorhabditis elegans is coordinated by interactions between the somatic gonad and germ cells. Myoepithelial sheath cells of the proximal ovary are smooth muscle-like cells, but the regulatory mechanism of their contraction is unknown. We show that contraction of the ovarian muscle requires tropomyosin and troponin, which are generally major actin-linked regulators of contraction of striated muscle. RNA interference of tropomyosin or troponin C caused sterility by inhibiting ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 62 publications
1
76
1
Order By: Relevance
“…2D-F) were specifically expressed in the myoepithelial sheath. We previously demonstrated that PAT-10 troponin C and Ce-kettin, a large immunoglobulinlike repeat protein, were also specific in the myoepithelial sheath (Ono and Ono, 2004;Ono et al, 2006). We found that the monoclonal antibody MH42 against UNC-89, a large obscurin-like thick-filament-associated protein (Benian et al, 1996), specifically stained the proximal myoepithelial sheath (Fig.…”
Section: Expression Patterns Of Cytoskeletal Proteins In the C Elegamentioning
confidence: 73%
See 4 more Smart Citations
“…2D-F) were specifically expressed in the myoepithelial sheath. We previously demonstrated that PAT-10 troponin C and Ce-kettin, a large immunoglobulinlike repeat protein, were also specific in the myoepithelial sheath (Ono and Ono, 2004;Ono et al, 2006). We found that the monoclonal antibody MH42 against UNC-89, a large obscurin-like thick-filament-associated protein (Benian et al, 1996), specifically stained the proximal myoepithelial sheath (Fig.…”
Section: Expression Patterns Of Cytoskeletal Proteins In the C Elegamentioning
confidence: 73%
“…2J-R). In addition, we previously reported that Ce-tropomyosin was expressed in the proximal myoepithelial sheath and the sper- matheca (Ono and Ono, 2004). All of these structural proteins, except for actin, were not significantly detected in the germline as observed at different focal planes (data not shown).…”
Section: Expression Patterns Of Cytoskeletal Proteins In the C Elegamentioning
confidence: 77%
See 3 more Smart Citations